Cybersquatting of UKM domains: ukm.biz; ukm.com; ukm.info; ukm.net; ukm.org - Zinatul Ashiqin Zainol,; Safinaz Mohd Hussein,; Siti Naaishah Hambali, (Fakulti Undang - Undang, 2003)

(untitled)
The deliberate, bad faith registration of domain names that violates a trade or service marks rights is not restricted to famous and well-known marks only, but personality names and names of institute of higher learning have also been vulnerable to such predatory practices. Two separate searches for the term ‘ukm’ using the WHOIS database reveal that four out of five of the generic top level domains, only one registrant has a legitimate interest to use ‘ukm’ for its domain name. Universiti Kebangsaan Malaysia should submit a complaint under the Uniform Dispute Resolution Proceedings (UDRP) to recover the relevant domain names